2021
DOI: 10.1186/s12865-020-00389-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Zika virus infection by antibodies from West Nile virus seropositive individuals with no history of clinical infection

Abstract: Background Recent outbreaks of Zika Virus (ZIKV) infection and associated microcephaly has raised multiple scientific questions. The close antigenic relatedness between flaviviruses makes diagnosis of specific infection difficult. This relatedness also raises the potential of Antibody Dependent Enhancement (ADE) via cross reactive antibodies to flaviviruses like West Nile Virus (WNV) and Dengue Virus (DENV). Asymptomatic WNV infections are endemic throughout the US creating a large proportion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
0
14
0
1
Order By: Relevance
“…Lately, several in vitro studies on ADE also reported that cross-reactive West Nile Virus (WNV) Abs enhance ZIKV infection ( 11 , 12 ) and that ZIKV Abs increase WNV, SLEV, Rocio virus (ROCV) and Ilheus virus (ILHV) infection ( 13 ). However, larger clinical studies in flavivirus endemic human populations are needed to establish the role of pre-existing flavivirus humoral responses with either a protective or detrimental role in subsequent flavivirus infections.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, several in vitro studies on ADE also reported that cross-reactive West Nile Virus (WNV) Abs enhance ZIKV infection ( 11 , 12 ) and that ZIKV Abs increase WNV, SLEV, Rocio virus (ROCV) and Ilheus virus (ILHV) infection ( 13 ). However, larger clinical studies in flavivirus endemic human populations are needed to establish the role of pre-existing flavivirus humoral responses with either a protective or detrimental role in subsequent flavivirus infections.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the prevalence of WNV infection in the United States, this may have a great potential risk. Further research found that the flavivirus E antibody is related to this cross ADE ( Garg et al, 2021 ).…”
Section: Ade Of Representative Virusmentioning
confidence: 99%
“…By now, the flavivirus West Nile virus (WNV) is the main medically relevant mosquito-borne viral threat in European and Eastern Mediterranean countries, being responsible for recurrent outbreaks of febrile illness and meningoencephalitis [ 16 , 17 ]. Interestingly, a diverse degree of cross-reactivity between ZIKV and WNV has been reported, going from a lack of cross-reactive immunity to ADE of infection, or even to heterologous cross-protection [ 8 , 14 , 18 , 19 , 20 , 21 , 22 ]. Therefore, ZIKV vaccine candidates that could be used to combat hypothetical future ZIKV outbreaks should consider the potential cross-reactions between WNV and ZIKV.…”
Section: Introductionmentioning
confidence: 99%